Dengue hemorrhagic fever: Knowledge, attitude, and practice in Palmeriam, Jakarta, Indonesia - Martina, Siska Evi; Bratajaya, Cicilia Nony Ayu; Ernawati, Ernawati (GHMJ (Global Health Management Journal), 2018)
Background: Dengue hemorrhagic fever (DHF) is the most rapidly spreading mosquito-borne viral disease in the world. It is an emerging disease, episodic and occurring annually.Aims: This study was to examine the knowledge, attitude, and practice of community in Palmeriam, Jakarta regarding dengue hemorrhagic fever.Methods: A community-based cross-sectional study was designed in this study between June to July 2016. Purposive sampling was done to collect data from 148 respondents.Results: This study found that average age was 47 years old, 75% were women, and 46.6% finished secondary high school. In another hand, 23.6% respondents had good knowledge, and 49.3% had a neutral attitude for preventing dengue hemorrhagic fever. The study found that 68.2% respondents had a mid-level of practice prevention dengue hemorrhagic fever and it can be improved. This study indicated that the community was quite familiar with Dengue hemorrhagic fever, but there was confusion about water storage and environment effect.Conclusion: Health promotion program and community participation should improve dengue awareness. Continuous campaign for enhancing the knowledge and attitude would result in better practice for DHF prevention. Keywords: Knowledge, Attitude, Practice, Dengue Hemorrhagic Fever. Received: 11 December 2017; Reviewed: 05 January 2018; Received in revised form: 14 February 2018: Accepted: 28 February 2018. DOI: https://doi.org/10.35898/ghmj-21184